Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1248
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Distant Supervision for Relation Extraction via Knowledge Graph Embedding

Abstract: Distant supervision is an effective method to generate large scale labeled data for relation extraction, which assumes that if a pair of entities appears in some relation of a Knowledge Graph (KG), all sentences containing those entities in a large unlabeled corpus are then labeled with that relation to train a relation classifier. However, when the pair of entities has multiple relationships in the KG, this assumption may produce noisy relation labels. This paper proposes a label-free distant supervision meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…Actually in Freebase, the triple format is like (e1, r, e2) where e1 and e2 are the two entities and r defines the relation. So relation can be found in a known KG and can generate large amount of data [4]. Since we mentioned before that we created our own Bangla Freebase which contains a large number of relation with the help of Wikidata query service and SPARQL query language.…”
Section: Creating Bangla Freebasementioning
confidence: 99%
“…Actually in Freebase, the triple format is like (e1, r, e2) where e1 and e2 are the two entities and r defines the relation. So relation can be found in a known KG and can generate large amount of data [4]. Since we mentioned before that we created our own Bangla Freebase which contains a large number of relation with the help of Wikidata query service and SPARQL query language.…”
Section: Creating Bangla Freebasementioning
confidence: 99%
“…independently proposed to use attention to address the same limitation, and Du et al (2018) improved by using multilevel self-attention. To account for the noise in distant supervision labels, ; ; Wang et al (2018) suggested different ways of using "soft labels" that do not necessarily agree with the distant supervision labels. Ye et al (2017) proposed a method for leveraging dependencies between different relations in a pairwise ranking framework, while arranged the relation types in a hierarchy aiming for better generalization for relations that do not have enough training data.…”
Section: Related Workmentioning
confidence: 99%
“…Many Knowledge Graphs (KGs), such as Freebase [2] and YAGO [33], have been built in recent years and led to a broad range of applications, including question answering [4], relation extraction [36], and recommender system [49]. KGs store facts as triples in the form of (subject entity, relation, object entity), abridged as (s, r, o).…”
Section: Introductionmentioning
confidence: 99%